Correctness of Multiplicative Additive Proof Structures is NL-Complete - de Naurois, P.J.; Mogbil, V. (2008 23rd Annual IEEE Symposium on Logic in Computer Science, 2008)
The authors revisit the correctness criterion for the multiplicative additive fragment of linear logic. We prove that deciding the correctness of corresponding proof structures is NL-complete.